Identifying nurse managers' essential information needs in daily unit operation in perioperative settings. Issue 3 (8th February 2020) - Siirala, Eriikka; Salanterä, Sanna; Lundgrén‐Laine, Heljä; Peltonen, Laura‐Maria; Engblom, Janne; Junttila, Kristiina
Abstract: Aim: To identify nurse managers' essential information needs in daily unit operation in perioperative settings. Design: Qualitative and quantitative descriptive design. Methods: The study consisted of (I) generation of an item pool of potential information needs, (II) assessment of the item pool by an expert panel and (III) confirming the essential information needs of nurse managers in daily unit operation with a survey ( N =  288). Content validity index values were calculated for the assessments by expert panel and in the survey. Internal consistency of the final item pool was explored with Cronbach's alpha. The data were collected from 2011–2015. Results: During the study process, the number of essential information needs decreased from 92–41. The final item pool consisted of 12 subthemes, and they were categorized into four main themes: patient's care process, surgical procedure, human resources and tangible resources. The findings can be used to create a knowledge map for information system purposes.